MACROECONOMY IMPACTS ON INTERNATIONAL TRADE BETWEEN INDONESIA AND ISLAMIC COUNTRIES - Al Mustofa, Muhammad Ubaidillah; Mawardi, Imron; Widiastuti, Tika; Ardiantono, Dewie Saktia (Universitas Airlangga, 2020)
As one of the members of the Organisation of Islamic Corporation (OIC), Indonesia has excellent trade prospects. Therefore, this study has a purpose to examine the impact of macroeconomics factors on trade between Indonesia and intra-OIC countries. The variables of macroeconomics in this study consist of country risks, inflation, exchange rate, oil price, and economic growth. Quantitative is the right method for this study, applying Ordinary Least Square (OLS) regression with the help of EViews. The data used for the analysis is a time horizon with annual frequency from 1986 to 2016. Furthermore, finding shows that almost all variables of macroeconomics play an insignificant role in determining the trade between Indonesia and Islamic countries. However, the oil price is the only variable to show its contribution towards trade between Indonesia and intra-OIC countries. The results indicate that macroeconomic variables do not contribute to the key decisions for conducting trade internationally. Political factors and bilateral treaties become better variables to explain Indonesia's trade with other Islamic countries. Keywords: Country Risk, International Trade, Macroeconomic, Organisation of Islamic Corporation, Indonesia.